Inkwizytor - Teatr Lalek (Białystok). ([Białystok] : [wydawca nieznany], 2007)
Plakat premiery 13.10.2007 r.
Miejsce i data wydania na podstawie treści.
Keywords: Teatr Lalek (Białystok) -- plakaty; Plakaty -- 1990-.